Knowledge, attitude and perception on cervical cancer among female students in Universiti Malaysia Sarawak (UNIMAS) - Kong, Sing Ling; Lai, Shu Xian; Mohd Ruduan, Mat Ghani; Muhammad Nur Hafiz, bin Azman (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This cross-sectional study aimed to assess knowledge, attitude and perception on HPV (Human papillomavirus), cervical cancer and their associations with socio-demographic characteristics among UNIMAS female students. Data were collected using questionnaires and the samples were selected by convenience. Analysis is done using SPSS 17.0 software. Fi e hundred respondents consented to participate in this study but only 418 completed it. Most of them were undergraduate (n=400, 95.7%), Malay (n=217, 51.9%), and Muslim (n=220, 52.6%) students. 101 (24.2%) of them were medical students while the remaining (n= 317, 76.8%) were non-medical students making the total of 418. Important findings in this study include poor knowledge on HPV and pap smear among female students in UNIMAS. Only 31 (7.4%) of the respondents have been vaccinated with HPV vaccine. Majority of the respondents (n=281, 95.9%) knew that HPV was transmitted sexually. There was no significant association between level of knowledge and races. However, Chinese respondents had a higher level of knowledge on HPV / cervical cancer probably due to the higher incidence rate of cervical cancer among Chinese women. Most of the respondents (0= 308, 73.7%) expressed their preference for a female doctor than a male doctor to perform pap smear on them. 316 or 80.6% ofthe respondents had poor knOWledge